DIRECTIVE AND EXPRESSIVE SPEECH ACTS USED BY TRAVIS PARKER IN THE CHOICE MOVIE - Teofanne Nurinik Wea; Barli Bram (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2022)
This paper aimed to explore the categories of speech acts used by Travis Parker as the main character of The Choice movie. Data were collected using a qualitative method and analyzed using a descriptive analysis technique. Results showed that the main character used directive and expressive speech acts. The directive ones included the acts of ordering, commanding, warning, suggestion, requesting, forbidding, and inviting. Specifically, the act of ordering something appeared once, commanding four times, giving a suggestion once, requesting twice, forbidding twice, and inviting someone once. Furthermore, the expressive function included the acts of apologizing, thanking, greeting, and compliment.  Specifically, the act of apologizing for someone appeared six times, giving thanks once, greetings three times, and giving a compliment three times.  Exploring the roles and context of speech acts in The Choice movie from a sociolinguistic perspective will contribute to English learning-teaching.